2012
DOI: 10.1371/journal.pone.0043333
|View full text |Cite
|
Sign up to set email alerts
|

Plexin-B2 and Plexin-D1 in Dendritic Cells: Expression and IL-12/IL-23p40 Production

Abstract: Plexins are a family of genes (A,B,C, and D) that are expressed in many organ systems. Plexins expressed in the immune system have been implicated in cell movement and cell-cell interaction during the course of an immune response. In this study, the expression pattern of Plexin-B2 and Plexin-D1 in dendritic cells (DCs), which are central in immune activation, was investigated. Plexin-B2 and Plexin-D1 are reciprocally expressed in myeloid and plasmacytoid DC populations. Plasmacytoid DCs have high Plexin-B2 but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 41 publications
5
49
1
Order By: Relevance
“…This set of data corroborated with those obtained in our study in patients with active UC, where we demonstrated that SEMA3E was negatively correlated with cells expressing CD11C and maturation markers IL12/IL23p19 . These findings are in agreement with previous data showing that a deficiency in SEMA3E receptors (plexin‐D1 and plexin‐B2) is associated with a negative regulation of IL‐12/IL‐23p40 in CD11C‐dendritic cells (DC; Holl et al, ). Moreover, Movassagh, Shan, Mohammed, et al () depicted that the deletion of Sema3e can enhance the recruitment of pulmonary DC and can result in a worsening of the allergic airway inflammation, associated with an increase in T‐cell activation.…”
Section: Discussionsupporting
confidence: 93%
“…This set of data corroborated with those obtained in our study in patients with active UC, where we demonstrated that SEMA3E was negatively correlated with cells expressing CD11C and maturation markers IL12/IL23p19 . These findings are in agreement with previous data showing that a deficiency in SEMA3E receptors (plexin‐D1 and plexin‐B2) is associated with a negative regulation of IL‐12/IL‐23p40 in CD11C‐dendritic cells (DC; Holl et al, ). Moreover, Movassagh, Shan, Mohammed, et al () depicted that the deletion of Sema3e can enhance the recruitment of pulmonary DC and can result in a worsening of the allergic airway inflammation, associated with an increase in T‐cell activation.…”
Section: Discussionsupporting
confidence: 93%
“…However, later we and others have demonstrated Plexin B1 and/or D1 expression in the immune system, particularly on DC (10,20), T cells (21) and Treg cells (our unpublished observations).…”
Section: Introductionsupporting
confidence: 53%
“…It has recently been revealed that Plexin-D1 is also expressed during B lymphocyte activation and enables these cells to respond to germinal center chemokines such as CXCL12, CXCL13 and CCL19 from the germinal center [29]. In dendritic cells, Plexin-D1 is a negative regulator of IL-12/IL-23p40 response [30]. …”
Section: The Role Of Sema3e and Plexin-d1 In The Development Of Othermentioning
confidence: 99%